Haloperidol Overdosing in the Treatment of Agitated Hospitalized Older People with Delirium: A Retrospective Chart Review from a Community Teaching Hospital - Zirker, William; Dorokhine, Igor; Knapp, Clifford M.; Patel, Nayan; Musuku, Mary (Drugs & aging, 2013)
Background Practice guidelines recommend the use of low dose haloperidol when medication is needed to treat delirium with acute agitation in hospitalized older people. Despite this, high dose haloperidol may frequently be used and result in higher rates of complications. Objective To describe dosages and effects of haloperidol used in the initial treatment of delirium with acute agitation in hospitalized older people, and prescriber use of low and high dose haloperidol. Methods Retrospective chart reviews were performed from June 2008 to May 2009 in a community teaching hospital located in Upland, PA, USA. Patients aged 65 years and older with acute agitated delirium were included. Patients admitted to ICU and those with psychiatric conditions were excluded. Data were collected on haloperidol dosing, responses, sedation, length of stay, and concurrent use of lorazepam. Results A total of 261 charts of patients who received haloperidol were reviewed and 56 patients met inclusion criteria (14 males, 42 females). The mean age of subjects was 83 years. The recommended starting dose of haloperidol (0.5 mg) was administered to 35.7 % of the patients. An initial dose of more than 1 mg was received by 37.5 % of the patients. The remaining 26.8 % of patients received 1 mg. The relative risk of sedation was significantly greater for subjects receiving more than 1 mg of haloperidol in 24 h. The length of hospitalization was not predicted by haloperidol doses or lorazepam but by the number of days of agitation. Conclusions Higher than recommended initial doses of haloperidol were frequently used in the treatment of delirium with acute agitation in hospitalized older people. We found no evidence to suggest that higher dosages were more effective in decreasing the duration of agitation or the length of hospital stay. Low dose haloperidol appears to be as effective as and safer than higher doses in the treatment of acute agitation in this older population.